Simple Switching Strategy for High-Torque Control Performance utilizing Neutral Point Clamped Multilevel Inverter - Alias, Nor Faezah; Jidin , Auzani; Razi, Atikah; Sutikno, Tole; Ismail, Huzainirah (2013)
Three-level Neutral Point Clamped (NPC) inverter allows the configuration of switching devices to operate at high voltage and produce lower current/voltage harmonics. It is known that, DTC of induction machine which employs hysteresis controller has major drawbacks namely larger torque ripple and variable switching frequency. This paper aims to propose a suitable voltage vector selection to provide better torque regulation and lower switching frequency by employing DTC with 3-level NPC multilevel inverter. A simple switching strategy was formulated using 7-level torque hysteresis and 2-level flux hysteresis controllers to give more options in selecting an appropriate voltagevector, inherently, according the motor operation conditions. The improvements offered were verified through simulations.